Is Appendectomy During Late Stages of Pregnancy Associated with an Increased Cesarean Delivery Rate? – a Retrospective Analysis of One Center During 10 Years - Kummer, Julia; Koenigbauer, Josefine; Peters, Falko Stephan Joachim; Rickert, Christian; Hellmeyer, Lars (Geburtshilfe und Frauenheilkunde, 2024)
About one in 500 pregnant women requires a surgical intervention that is not pregnancy-related. One of the most common surgical interventions during pregnancy is appendectomy. The primary aim of this study was to assess surgical access of appendectomy during pregnancy and pregnancy outcome. Secondary outcomes were clinical symptoms and diagnostics as well as histopathological analysis.This is a single-center retrospective data analysis conducted at a tertiary perinatal center. A digital search of the hospital record archive was conducted focusing on pregnant women beyond 24 0/7 weeks of pregnancy encoding appendectomy. Descriptive statistical analysis was performed.Between January 2013 and January 2023, a total of 20 appendectomies were performed during pregnancy with gestational age beyond 24 0/7 weeks of pregnancy. All of them were performed as lower midline laparotomy. The rate of appendix perforation was 3/20 (15.0%). 19/20 patients (95.0%) delivered via cesarean. In 7/20 patients (35.0%) appendectomy was performed during cesarean delivery due to incidental finding of irritated or abnormal vermiform appendix. In the pathological work-up, only 2/7 (28.6%) of these subjects had inflammation.In this small monocentric cohort, only open appendectomies were performed. Our data indicate that it is safe to perform open appendectomy during pregnancy if necessary. In this small patient group, there was an increase in simultaneous cesarean deliveries.
Keywords: appendectomy in pregnancy; appendicitis in pregnancy; cesarean section; surgical intervention pregnancy; imaging diagnostics appendicitis